Assessment of the microbiota in persistent periapical lesions and its clinical implications - Alshargawi, Waleed Khalid; Alfawzan, Samaher Khaled; Alrobayan, Ghalya Abdulrahman; Alsuwailem, Faisal Abdullah; Almishari, Fatimah Salman; Kanzou, Mahfoud Samer; Alqahtani, Abdulrahman Ali; Alruwaili, Razan Turki (International Journal Of Community Medicine And Public Health, 2025)
Persistent periapical lesions are chronic inflammatory conditions characterized by microbial colonization, immune responses and progressive tissue destruction. These lesions, often resistant to conventional endodontic therapy, are associated with diverse microbial communities, including anaerobic bacteria, fungi and viruses. Advanced diagnostic tools such as cone-beam computed tomography (CBCT) and next-generation sequencing have significantly improved lesion detection and microbial profiling, enabling precise treatment planning. CBCT provides detailed imaging of lesion size and bone loss, while molecular diagnostics reveal complex microbial compositions, including unculturable species and resistance genes. The therapeutic management of persistent lesions involves mechanical debridement, antimicrobial agents and emerging adjuncts. Sodium hypochlorite, chlorhexidine and bioceramic sealers are effective in disrupting biofilms and enhancing sealing properties. Advanced modalities such as antimicrobial photodynamic therapy and probiotics offer innovative approaches to combat resistant pathogens and restore microbial balance. Regenerative strategies, including stem cell therapies and platelet-rich fibrin, show promise for restoring periapical tissue structure and function. Prognostic evaluation relies on lesion size, microbial diversity and systemic health factors. Larger lesions and those linked to systemic conditions like diabetes exhibit lower healing rates, emphasizing the need for comprehensive care. Chronic inflammation from periapical lesions has broader systemic implications, including associations with cardiovascular disease and diabetes, necessitating interdisciplinary collaboration. Future directions in managing persistent periapical lesions include artificial intelligence-driven diagnostics and personalized treatment strategies. Artificial intelligence can enhance predictive analytics, while regenerative approaches aim to repair biological tissues rather than replace them mechanically. Together, these advancements highlight the need for integrated, evidence-based approaches to improve outcomes in the diagnosis, treatment and prognosis of persistent periapical lesions. This integrated understanding bridges the gap between clinical management and the broader systemic implications of chronic oral infections.